2019
DOI: 10.1002/pssa.201900151
|View full text |Cite
|
Sign up to set email alerts
|

Annealing and LEEBI Effects on the Stacking Fault Expansion and Shrinking in 4H‐SiC

Abstract: The expansion of generated by indentation Shockley‐type stacking faults (SSFs) due to e‐beam irradiation is studied. It is shown that SSFs can expand even outside the irradiation region. The dislocation velocity is independent of SSF size and practically linear increases with beam current. These results allow to conclude that the dislocation glide is enhanced by the excess carrier recombination. It is shown that the driving force for the SSF expansion is mainly determined by the energy gain due to electron cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Moreover, the size of this region does not practically depend on the position of the beam outside or inside SSFs, although the observation of bright EBIC contrast seems to suggest [42,43] that the transport length of excess carriers increases along the SSFs. Probably, this increase does not exceed 1 µm and the carrier transport along SSFs cannot be the main reason for their expansion outside the irradiated area on the distances of several tens of microns [14,33,44]. As shown below, other reason for such expansion can be proposed.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, the size of this region does not practically depend on the position of the beam outside or inside SSFs, although the observation of bright EBIC contrast seems to suggest [42,43] that the transport length of excess carriers increases along the SSFs. Probably, this increase does not exceed 1 µm and the carrier transport along SSFs cannot be the main reason for their expansion outside the irradiated area on the distances of several tens of microns [14,33,44]. As shown below, other reason for such expansion can be proposed.…”
Section: Resultsmentioning
confidence: 96%
“…Such assumption allows to explain the SSF expansion on the distances up to about 50 µm outside the irradiated area [14,33,44]. Additionally, it helps to understand the extremely small activation energy for the REDG in 4H-SiC because in this case to enhance the dislocation glide the kink formation energy should be only lowered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 33 ] In contrast, as predicted by theoretical studies, [ 34,35 ] the barrier for the kink migration can be of about 30–60 meV for some core configurations (e.g., symmetrically reconstructed), [ 34 ] i.e., low enough to migrate at room temperature. Besides, as shown in, [ 14,36,37 ] SSFs can expand beyond the irradiated region at distances significantly exceeding the diffusion length that was explained by the enhanced excess carrier transport along SSFs. However, as shown in, [ 15 ] the increase in the SSF width under its direct excitation was smaller than that under excitation of Si‐core PD.…”
Section: Introductionmentioning
confidence: 94%
“…[33] In contrast, as predicted by theoretical studies, [34,35] the barrier for the kink migration can be of about 30-60 meV for some core configurations (e.g., symmetrically reconstructed), [34] i.e., low enough to migrate at room temperature. Besides, as shown in, [14,36,37] SSFs can expand beyond the irradiated region at distances significantly exceeding the Single-layer Shockley-type stacking fault (SSF) expansion in 4H-SiC due to irradiation by a focused e-beam in the scan mode with a different rate and at fixed points has been studied. It is shown that the focused e-beam enhances the 30°S i-core partial dislocation glide at room and liquid nitrogen temperatures only at distances smaller than about 10 μm.…”
Section: Introductionmentioning
confidence: 99%